Conversion of Sodium Lactate to Lactic acid and Sodium Hydroxide with Cation Exchange Membrane Electrolytic Cell - R Sirisangsawang; P Samaikaew; B Chotiviriyavanich; P Kitchaiya (My University, 2019)
Abstract This research conversion of sodium lactate to lactic acid and sodium hydroxide with electrolysis technique combined with cation exchange membrane (CEM). The electrolytic cell has effective membrane area of 144 cm 2 . Experiments were carried out by feeding sodium lactate solution which was prepared with alkaline degradation of invert sugar. This solution was feed through the anolyte. The process was studied in terms of the initial concentration of sodium lactate (i.e. 0.75, 1.20 and 1.50 M) and the applied voltage (i.e. 4, 6 and 8 volt) to assess the efficiency of separation. The results suggested that the transport of sodium ion through the membrane was proportional to the applied voltage but it was not depend on sodium lactate concentration which was used as feed. The current efficiency increased as the applied voltage increased. Conversely, the energy consumption with respect to sodium hydroxide production increased with both factors. From this experiment, it was found that the highest lactic acid recovery was 55.5% at 4 volt and initial lactate concentration of 0.75 M.
Keywords: Sodium hydroxide; Sodium lactate; Alkaline water electrolysis; Membrane-based Ion Separation Techniques